Kasr Alainy simplified uterine preserving surgery for conservative management of placenta accreta spectrum (PAS): A modified surgical approach. (May 2023) - Mousa, Abdalla; Elkhateb, Islam T.; Gaafar, Hassan M.; Elsherbini, Moutaz M.; Mousa, Hatem; Abdalla, Mostafa; Abdelbar, Ahmed; Rida, Dana; Majd, Hooman Soleymani; Collins, Sally L.
Abstract: Objective: The incidence of placenta accreta spectrum (PAS) is rising rapidly due to the global surge in Caesarean delivery. It is associated with significant maternal morbidity and mortality. It is usually managed with Caesarean hysterectomy. However, uterine preserving surgeries can have advantages over Caesarean hysterectomy and intentional placental retention techniques. Study design: We present a modified technique of uterine preserving surgery that uses a safe approach for placental bed surgical devascularization. This is followed by resection of the invaded uterine segment and uterine wall reconstruction. Results: The technique was used in the management of 20 patients with antenatally suspected PAS that were confirmed at laparotomy. It was successful in preserving the uterus in 18/20 (90 %) women. The mean intraoperative blood loss in was 1305 CC (SD: + 361.6) with a mean operative time of 123 min (SD: ±38.7). There was only one urinary bladder injury and no other maternal morbidity. Conclusion: Our surgical technique is safe and may be useful for conservative surgical management of PAS, particularly in low- and middle-income countries, where access to complex resources, such as interventional radiology, is limited.